Puerarin Exerts Protective Effects on Wear Particle-Induced Inflammatory Osteolysis - Yang, Chao; Li, Juehong; Zhu, Kechao; Yuan, Xiangwei; Cheng, Tao; Qian, Yebin; Zhang, Xianlong (Frontiers in Pharmacology, 2019)
Wear particle-stimulated inflammatory bone destruction and the consequent aseptic loosening remain major postoperative problems for artificial joints. Studies have indicated that puerarin promotes osteogenesis and alleviates lipopolysaccharide-induced osteoclastogenesis in vitro. However, the underlying molecular mechanism by which puerarin interacts with receptor activator of nuclear factor kappa-B ligand (RANKL)-mediated osteoclast formation in vitro and wear particle-stimulated osteolysis in vivo has not been reported. In this work, the protective effects exerted by puerarin on titanium particle-stimulated bone destruction in vivo and on RANKL-induced osteoclast activation in osteoclastic precursor cells in vitro were investigated. As expected, puerarin significantly inhibited wear particle-mediated bone resorption and proinflammatory cytokine productions in a calvarial resorption model. Additionally, puerarin inhibited RANKL-induced osteoclast activation, bone resorption ability, and F-actin ring formation in vitro as puerarin concentration increased. Furthermore, mechanistic investigation indicated that reduced RANKL-stimulated MEK/ERK/NFATc1 signaling cascades might regulate the protective effect of puerarin. Conclusively, these results indicate that puerarin, a type of polyphenol, might serve as a protective agent to prevent osteoclast-related osteolytic diseases.